1978
DOI: 10.1021/i260067a010
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst Deactivation by Pore Structure Changes. The Effect of Coke and Metal Depositions on Diffusion Parameters

Abstract: Diffusion data involving different sized hydrocarbon molecules in three different alumina based pellets are presented. One of the samples has not been used in any reactions, while the two other samples are the same pellets as the unused ones, except that they have been used for the hydrocracking of residuum under varying conditions of high temperature and pressure for several days. The results of the diffusion studies show that the used pellets exhibited severe reduction in intraparticle diffusion characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
1

Year Published

1985
1985
1990
1990

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 13 publications
2
23
1
Order By: Relevance
“…The catalyst fouling rate of HY zeolite in vapor phase was greater than that of silica alumina (Marczewski and Wojciechowski, 1982;Hano et al, 1975). The difference in the catalyst fouling rate between HY zeolite and silica alumina are caused by differences in concentration of strong acid sites and in diffusional limitation of reactant or product by coke deposition (Prasher et al, 1978;Rajagopalan and Luss, 1979). However, the observed deactivation coefficients for HY zeolite are smaller than those of silica alumina, and they tend to be proportional to the reaction rates.…”
Section: Discussionmentioning
confidence: 99%
“…The catalyst fouling rate of HY zeolite in vapor phase was greater than that of silica alumina (Marczewski and Wojciechowski, 1982;Hano et al, 1975). The difference in the catalyst fouling rate between HY zeolite and silica alumina are caused by differences in concentration of strong acid sites and in diffusional limitation of reactant or product by coke deposition (Prasher et al, 1978;Rajagopalan and Luss, 1979). However, the observed deactivation coefficients for HY zeolite are smaller than those of silica alumina, and they tend to be proportional to the reaction rates.…”
Section: Discussionmentioning
confidence: 99%
“…There have been a number of studies (Beck and Schultz, 1970;Prasher and Ma, 1977;Prasher et al, 1978;Thrash and Pildes, 1981;Deen et al, 1981;Galiasso and Morales, 1983) which have reported effective diffusivities of liquids within the pore structure of catalysts and other solids. The data in some studies (Sanerfield et al, 1973;Chantong and Massoth, 1983;Baltus and Anderson, 1983;Seo and Massoth, 1985) have generally been correlated by empirical equations of the type * *…”
mentioning
confidence: 99%
“…Both factors can account for the low diffusivity values obtained for the aged crushed catalysts. Prasher et al (1978) report diffusivities at 298 K for a number of aromatic compounds to be lowered by a factor of four to five for a catalyst exposed to resid for several days (probably containing mostly coke and little metals).…”
Section: Discussionmentioning
confidence: 98%